Assessment of the State of the Information and Communication Technology Sector in the Northern Regions of Russia Using Multidimensional Grouping - Evgeniy N. Timushev (Арктика и Север)
The paper analyzes the state of the information and communication technologies (ICT) sector in the northern regions of Russia. The main research methods are multidimensional grouping and comparative analysis of ICT development. The relevance of the study is due to the lack of knowledge about the state of information and communication technologies in the northern regions of Russia. At the same time, ICT has a great potential to stimulate the economic development of the North of Russia and the Arctic in par-ticular. The novelty of the work lies in the development of a methodological approach to the comparative analysis of the ICT sector in the Russian regions, aimed at identifying problem areas of development. An original set of indicators is created — criteria for the state of ICT at the regional level. The validity of this set is proved by the method of factor analysis. Multidimensional grouping of all subjects of the Russian Federation according to the selected indicators is performed with an emphasis on the northern regions. It is revealed that the northern regions have higher values of ICT indicators compared to other regions of Russia due to the social sphere and the state of ICT at the household level. The leaders are the Yamalo-Nenets Autonomous Okrug, the Khanty-Mansi Autonomous Okrug and the Republic of Karelia. Practical recommendations for ICT development in the northern regions are formulated. The main reserves of ICT development in the North are identified — growth of state and municipal services provision in electronic form and digitalization of health care institutions.